Ganong's review of medical physiology - Barrett, Kim E.; Barman, Susan M.; Boitano, Scott; Brooks, Heddwen L. (A Lange medical book., 2010)
The field's most complete, up-to-date, and engagingly-written text on medical physiology, now in full color. This 23rd edition is an excellent source of the current knowledge in physiology. So many students in the future will be able to use this book to enhance their knowledge. For more than four decades, "Ganong's Review of Medical Physiology" has been the leader in helping medical students and clinicians understand the fascinating subject of human and mammalian physiology. Concisely covering every important topic without sacrificing depth or readability, "Ganong's" delivers more detailed, clinically-relevant, high-yield information per page than any similar text or review. Thoroughly updated to reflect the latest research and developments in important areas such as the cellular basis of neurophysiology.